On-Site Measurement on Compaction Characteristics of Coal Gangue and Surface Subsidence Disaster in Deep Backfilling Mining - Wang, Jiaqi; Zhang, Qiang; Yin, Wei; Qi, Shengming; Gao, Difa; Ma, Dan (Frontiers in Earth Science, 2021)
Gangue is the main backfilling material in solid backfilling mining, and its compaction characteristics determine the overburden control effect and surface subsidence. Under the action of compaction force and overburden pressure, the gangue will be broken, rotated and occluded, resulting in different compaction characteristics of gangue in the field and laboratory. To this end, a laboratory gangue compaction test system was established to test the compaction characteristics of gangue in the laboratory, such as stress-strain, stress bulk density and stress deformation modulus. Based on actual geological conditions of backfilling mining in the Tangshan coal mine, the characteristics of stress deformation modulus of gangue under different inclination angles and mining heights were tested on-site. Through the Beidou satellite CORS system, the surface subsidence of working face F5001was monitored. The research results show that the stress deformation modulus of gangue measured in the field is slightly less than that measured in the laboratory, and it is maintained at about 27 MPa under the overburden pressure in the on-site measurement. Backfilling technology with an initial compaction force of 2.5MPa can be used to effectively control the surface subsidence, and the maximum subsidence value is only 61 mm.